Contractile Detrusor’s Activity in Rats with Bladder Outlet Obstruction After Administration of Cortexin and Biologically Active Products of Mantle Gliocytes Culture - Globa, Vyacheslav Yu.; Rudik, Dem'yan Yu.; Ali, Sabina G.; Bozhok, Galina A.; Lehach, Evgen I. (Problems of Cryobiology and Cryomedicine, 2018)
Probl Cryobiol Cryomed 2018; 28(2): 172